Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Terhadap Rumah Makan Mie Mandes Cokro Bangkalan - Joko Septaryanto (Universitas PGRI Madiun, 2021)
This study aimed to determine factors consisted of service, price and product simultaneusly and partially affect the consumer satisfaction at Mie Mandes Restaurant Cokro Bangkalan. In this study used descriptive quantitative, the analytical method used multiple linear regression analysis, the population was one hundred people, the sample was fifty respondents, and sampling technique used Non Probality. The result showed that simultaneously all variables had an effect consumer satisfaction an Mie Mandes Restaurant Cokro Bangkalan, while the partial price is a variable that had a significant effect on consumer satisfaction.